2017
DOI: 10.3390/s17040938
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the Correlative Atomic Force Microscopy and Optical Microscopy

Abstract: Atomic force microscopy (AFM) has evolved from the originally morphological imaging technique to a powerful and multifunctional technique for manipulating and detecting the interactions between molecules at nanometer resolution. However, AFM cannot provide the precise information of synchronized molecular groups and has many shortcomings in the aspects of determining the mechanism of the interactions and the elaborate structure due to the limitations of the technology, itself, such as non-specificity and low i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 74 publications
1
38
0
Order By: Relevance
“…20,24,27 While not attaining the resolution of AFM, fluorescence microscopy provides high detection selectivity enabled by fluorescence tagging. 28 Correlative AFM and fluorescence microscopy can localize NPs in relation to other fluorescently tagged biomolecules with very high spatial resolution and detection selectivity. The correlative approach has been used to characterize phase segregation in SLBs 29,30 and membrane restructuring due to the addition of ceramide, 31,32 as well as to study the impact of 2,4-dichlorophenoxyacetic acid on bacterial, fungal, and human cells 33 and localize labeled fusion proteins within mammalian cells.…”
Section: Introductionmentioning
confidence: 99%
“…20,24,27 While not attaining the resolution of AFM, fluorescence microscopy provides high detection selectivity enabled by fluorescence tagging. 28 Correlative AFM and fluorescence microscopy can localize NPs in relation to other fluorescently tagged biomolecules with very high spatial resolution and detection selectivity. The correlative approach has been used to characterize phase segregation in SLBs 29,30 and membrane restructuring due to the addition of ceramide, 31,32 as well as to study the impact of 2,4-dichlorophenoxyacetic acid on bacterial, fungal, and human cells 33 and localize labeled fusion proteins within mammalian cells.…”
Section: Introductionmentioning
confidence: 99%
“…Current research mainly is focused on the understanding of biological processes at the nanoscale, as recognition of molecules and their properties with no labeling and the interaction among them [22][23][24]. This mini review revealed that only few papers deals with inner cell structure in situ.…”
Section: Discussionmentioning
confidence: 99%
“…Sample preparation procedures for exvivo microscopy differ substantially across the technologies and even within a modality; AFM images alone, for example, can be acquired under various conditions (vacuum, atmosphere, and liquid). Correlative imaging usually requires modality-specific preparation and setup trade-offs, such as between preservation of fluorescence and subcellular architecture for CLEM, between the AFM laser and excitation spectra of the used fluorophores to avoid bleaching for correlative AFM [78], or between preservation of fluorescence and X-ray contrast for correlative CT. Dependent on the used technology, the sample preparation needs to be adapted.…”
Section: Novel CMI Pipelinesmentioning
confidence: 99%